Exploring a New Narratological Paradigm for the Analysis of Narrative Communication in Translated Children’s Literature - Kruger, Haidee (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
Current contributions attempting to draw together translation studies and narratology are based almost exclusively on structuralist narratology, proceeding from the assumption that changes on the micro-level of the text will result in changes to the various narrative dimensions of the text, and will lead to a different configuration of the narrative communication situation in translated texts as compared to original works. However, it is argued in this paper that this approach, firstly, results in a conceptualisation of the narrative communication situation for the translated text that is particularly unwieldy and becomes even more so when considered in the context of translated children’s literature. Secondly, this approach does not take adequate cognisance of the role (or potential role) of the reader and the context, leaving both these aspects largely outside the process of analysis. Methodologically, it also means that narratological shifts in translation are mostly identified by means of comparative analysis, which, while useful, leaves the natural reading situation (where readers do not usually have access to the source text) out of consideration. Instead, this paper presents a preliminary and exploratory investigation of an alternative narratological framework that includes the reader as a constitutive component. The framework, based on the ideas of Bortolussi and Dixon (2003), proposes a two-part, interlocked conception of narratological elements: textual features and reader constructions. It is argued that such a framework provides a simultaneously simpler and more sophisticated means of understanding narrative communication in translated children’s literature. Firstly, translations and their source texts may be analysed comparatively in terms of their textual features, which may reveal the presence of the translator. However, the second dimension of the proposed framework posits that despite the fact that translation shifts effect changes in narrative features, child and adult readers’ responses to translated children’s texts do not necessarily and by default incorporate an awareness of the presence of an additional “voice” in the text, that of the translator. At this point the framework departs from standard narratological approaches to narrative communication in translated texts in proposing the necessity of investigating reader constructions rather than textual features alone.